2021
DOI: 10.1097/aud.0000000000001073
|View full text |Cite
|
Sign up to set email alerts
|

X-linked Malformation Deafness: Neurodevelopmental Symptoms Are Common in Children With IP3 Malformation and Mutation in POU3F4

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 89 publications
0
28
0
Order By: Relevance
“…POU3F4 encodes a POU-domain TF expressed in mesenchymal cells of the otic capsule, responsible for normal inner ear development [ 21 , 22 ]. POU3F4 mutant mice have reduced endocochlear potential and alterations in cochlear spiral ligament fibrocytes [ 23 ], leading to hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…POU3F4 encodes a POU-domain TF expressed in mesenchymal cells of the otic capsule, responsible for normal inner ear development [ 21 , 22 ]. POU3F4 mutant mice have reduced endocochlear potential and alterations in cochlear spiral ligament fibrocytes [ 23 ], leading to hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous reports on CI in patients with POU3F4 variants, detailed information is lacking and the postoperative outcomes have been highly variable. Choi et al [ 25 ] and Smeds et al [ 22 ] reported that patients with POU3F4 variants had improved speech scores after implantation but the scores were still lower than those of age-matched cohorts without apparent cochlear anomalies. These results differ from those reported by Tian et al [ 27 ] and Kang et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOX2 has also been implicated in nervous system development and its disruption can lead to profound deficits in cognition, vision, and motor function 50 . Interestingly, POU3F4 has primarily been implicated in the development of semicircular canals and inherited deafness [51][52][53][54] but has also been linked to deficits in cognition and mental health (including attention deficit hyperactivity and developmental language disorder) which are significantly comorbid with this form of deafness 55 . These non-auditory deficits are more profound than those observed in controls with other forms of deafness, suggesting that POU3F4 provides a common molecular aetiology underlying aspects of both central and peripheral nervous system development 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete partition type III is the only malformation of the inner ear for which X-linked inheritance linked to the mutation of the POU3F4 gene is recognized (28). It is characterized by a normal external morphology of the cochlea with the absence of internal architecture, in particular the modiolus and the bottom of the internal auditory canal are absent.…”
Section: Incomplete Partition Type IIImentioning
confidence: 99%